Determinants of substrate specificity in a catalytically diverse family of acyl-ACP thioesterases from plants - Rebecca S. Kalinger; Owen Rowland (BMC Plant Biology, 2023)
Abstract Background ACYL-LIPID THIOESTERASES (ALTs) are a subclass of plastid-localized, fatty acyl-acyl carrier protein (ACP) thioesterase enzymes from plants. They belong to the single hot dog-fold protein family. ALT enzymes generate medium-chain (C6-C14) and C16 fatty acids, methylketone precursors (β-keto fatty acids), and 3-hydroxy fatty acids when expressed heterologously in E. coli. The diverse substrate chain-length and oxidation state preferences of ALTs set them apart from other plant acyl-ACP thioesterases, and ALTs show promise as metabolic engineering tools to produce high-value medium-chain fatty acids and methylketones in bacterial or plant systems. Here, we used a targeted motif-swapping approach to explore connections between ALT protein sequence and substrate specificity. Guided by comparative motif searches and computational modelling, we exchanged regions of amino acid sequence between ALT-type thioesterases from Arabidopsis thaliana, Medicago truncatula, and Zea mays to create chimeric ALT proteins. Results Comparing the activity profiles of chimeric ALTs in E. coli to their wild-type counterparts led to the identification of interacting regions within the thioesterase domain that shape substrate specificity and enzyme activity. Notably, the presence of a 31-CQH[G/C]RH-36 motif on the central α-helix was shown to shift chain-length specificity towards 12–14 carbon chains, and to be a core determinant of substrate specificity in ALT-type thioesterases with preference for 12–14 carbon 3-hydroxyacyl- and β-ketoacyl-ACP substrates. For an ALT containing this motif to be functional, an additional 108-KXXA-111 motif and compatible sequence spanning aa77–93 of the surrounding β-sheet must also be present, demonstrating that interactions between residues in these regions of the catalytic domain are critical to thioesterase activity. The behaviour of chimeric enzymes in E. coli also indicated that aa77–93 play a significant role in dictating whether an ALT will prefer ≤10-carbon or ≥ 12-carbon acyl chain-lengths, and aa91–96 influence selectivity for substrates of fully or partially reduced oxidation states. Additionally, aa64–67 on the hot dog-fold β-sheet were shown to be important for enabling an ALT to act on 3-hydroxy fatty acyl-ACP substrates. Conclusions By revealing connections between thioesterase sequence and substrate specificity, this study is an advancement towards engineering recombinant ALTs with product profiles suited for specific applications.